2021
DOI: 10.31234/osf.io/e2z5m
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Xie, Liu, & Jaeger (2020). Cross-talker generalization during foreign-accented speech perception

Abstract: Speech perception depends on the ability to generalize previously experienced input effectively across talkers. How such cross-talker generalization is achieved has remained an open question. In a seminal study, Bradlow & Bent (2008, henceforth BB08) found that exposure to just five minutes of accented speech can elicit improved recognition that generalizes to an unfamiliar talker of the same accent (N=70 participants). Cross-talker generalization was, however, only observed after exposure to multiple … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 91 publications
0
1
0
Order By: Relevance
“…Previous work has often used lexical decision tasks during exposure (e.g., Kraljic & Samuel, 2005; Liu & Jaeger, 2018; Norris et al, 2003; Zhang & Samuel, 2014), though perceptual recalibration has also been found for a broad variety of different tasks during exposure (e.g., passive listening with catch trials, e.g., Bertelson, Vroomen, & De Gelder, 2003; Vroomen et al, 2007; ABX discrimination, Clarke-Davidson, Luce, & Sawusch, 2008; categorization, Clayards, Tanenhaus, Aslin, & Jacobs, 2008; Kleinschmidt et al, 2015; for further review and comparison of various paradigms, see Drouin & Theodore, 2018). Here we use a transcription task during exposure, a paradigm often used in related work on accent adaptation (e.g., Baese-Berk, Bradlow, & Wright, 2013; Bradlow & Bent, 2008; Tzeng, Alexander, Sidaras, & Nygaard, 2016; Xie, Liu, & Jaeger, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…Previous work has often used lexical decision tasks during exposure (e.g., Kraljic & Samuel, 2005; Liu & Jaeger, 2018; Norris et al, 2003; Zhang & Samuel, 2014), though perceptual recalibration has also been found for a broad variety of different tasks during exposure (e.g., passive listening with catch trials, e.g., Bertelson, Vroomen, & De Gelder, 2003; Vroomen et al, 2007; ABX discrimination, Clarke-Davidson, Luce, & Sawusch, 2008; categorization, Clayards, Tanenhaus, Aslin, & Jacobs, 2008; Kleinschmidt et al, 2015; for further review and comparison of various paradigms, see Drouin & Theodore, 2018). Here we use a transcription task during exposure, a paradigm often used in related work on accent adaptation (e.g., Baese-Berk, Bradlow, & Wright, 2013; Bradlow & Bent, 2008; Tzeng, Alexander, Sidaras, & Nygaard, 2016; Xie, Liu, & Jaeger, 2019).…”
Section: Methodsmentioning
confidence: 99%